Sistem Informasi Persediaan Domba Pada Asosiasi Kelompok Ternak Domba Secang Grabag Berbasis Google Maps - Setyo Pamungkas; M Lutfi MA; Fatkhurrochman (Julia: Jurnal Ilmu Komputer An Nuur, 2026)
The dissemination of information related to the location and availability of sheep within livestock group associations is still carried out manually, making it less effective and hindering consumers from obtaining accurate information. This study aims to design and develop a Sheep Inventory Information System based on Google Maps to help livestock groups disseminate information interactively and improve data accessibility for the public. The system was developed using the Waterfall model, with modeling through Unified Modeling Language (UML) and database design using Entity Relationship Diagram (ERD). It was built using the PHP programming language with the CodeIgniter framework and a MySQL database. Testing was conducted using the Black Box Testing method. The results show that all system functions run properly, and user evaluation using the Likert scale obtained a feasibility percentage of 86%, which is categorized as highly feasible.